Lady Chatterley's legacy in the movies : sex, brains and body guys - Lehman, Peter; Hunt, Susan (Rutgers University Press, 2010)
A new "body guy" genre has emerged in film during the last twenty years-a working-class man of the earth or bohemian artist awakens and fulfills the sexuality of a beautiful, intelligent woman frequently married or engaged to a sexually incompetent, educated, upper-class man. Lady Chatterley's Legacy in the Movies relates a host of wide-ranging films to a literary tradition dating back to Lady Chatterley's Lover and an emerging body culture of our time. The authors argue that the hero's body, lovemaking style, and penis-revealed through extensive male nudity-celebrate conform.